SAZAN is ancestor of domestic CARP - Usmonova Dilnoza Barotovna (Genius Journals, 2023)
One of the main reasons hindering the intensive development of domestic fish farming is the lack of high-quality fish stock. In many ways, this is a consequence of the violation and, to a certain extent, the imperfection of the applied technologies for growing young, including larvae. Currently, an alternative to traditional pond rearing is a relatively new method of rearing larvae of cyprinids under controlled (factory) conditions However, information about them is far from sufficient for success in rearing, despite the significant number of works devoted to this problem (Baranova, 1979; Brett, 1983; Vlasov, 1985; Konstantinov et al., I990; Zentazius, I984; Meske, 1985 Hasan , Macintosh .,, 1993 and others). Thus, the effect of light conditions on the growth rate and viability of larvae of cyprinids 1 has been studying, the effect has not been sufficiently studied; temperature: on the efficiency of utilization of feed, differing in the content of lipids in them. But, the most important, defining: an element of factory rearing, in our opinion; is the feeding of the larvae. Moreover, due to the low efficiency of the process of cultivating or catching live food, the problem of replacing it with dry: compound feed is very relevant. Despite the fact that it is fundamentally solved for the larvae of cyprinids (Dementiev and Sklyarov 1980; Ostroumova et al. 1984; Kanidiev et al. 1984; Dabrowski 1984; Bergot et al 1986), numerous publications indicate that: starter feeds are still inferior in their effectiveness to live feeds and, at best, provide; only satisfactory result
Keywords: cyprinid fish larvae; Asian strain; Domesticated carp